KONSEP PEMBELAJARAN PKN DALAM MENANAMKAN PENDIDIKAN ANTI KORUPSI SEJAK DINI DISEKOLAH DASAR - Chairiyah Chairiyah; Nadziroh Nadziroh; Wachid Pratomo (Universitas Sarjanawiyata Tamansiswa, 2017)
Corruption has become a disease harmful to the nation, the education transformation is required in order to reduce the growing corruption. One of them by integrating anti-corruption education into a number of subjects Education Anti-corruption one can be applied in teaching Citizenship Education. Anti-corruption values taught in the learning process Citizenship Education includes the value of honesty, discipline values, values of openness, and the value of responsibility. On the implementation of the Anti-Corruption Education in Citizenship Education learning by means of the application in the vision and mission, school culture that includes a variety of behavioral activities of the school community, canteens honesty and discipline and responsibility. Some of the factors obstacles, such as lack of awareness of students, was their habit of corrupt behavior. There are several ways that can be used to overcome the barriers as well as the efforts made in the Anti-Corruption Education in Learning Civic Education, that is: exemplary, habituation, giving strict sanctions, competition and sources, increased faith.